Multi-dimensional barrier identification for wind farm repowering in Spain through an expert judgment approach. (June 2022) - de Simón-Martín, Miguel; Ciria-Garcés, Tomás; Rosales-Asensio, Enrique; González-Martínez, Alberto
Abstract: Spain was one of the pioneers in the deployment of wind energy systems worldwide and thus since 2014 has a potential for repowering that reaches between 3.3 and 8.7 GW in 2021 (12%–32% of its current installed wind capacity). However, despite the technical and economic advantages, we have observed little interest from promoters in the repowering of already amortized wind farms. The aim of the proposed study is to depict the background framework of barriers for repowering wind farms, which is specially affecting to Spain, but that can also extend to other EU countries. Therefore, we conducted a systematic survey study with academics, promoters, financial experts, manufacturers, operators, maintainers and policymakers to identify and understand the existing real and practical barriers. As a result, we have identified 34 major barriers covering five categories: technical issues, economics, environmental considerations, social concerns, and regulatory and administrative hurdles. We then asked the experts to rate these barriers based on their impact or relevance. We found that the experts agree that regulatory and administrative barriers have the maximum impact, while economic, environmental and technical barriers have only a mid-high impact. Therefore, we can conclude that, in general, the Administration must develop a concise and stable regulatory framework for all RES, especially for repowering projects, and carry out a review of both the technical requirements and the incentives schemes, with a focus on energy efficiency. Highlights: We identify and score technical, economic, regulatory, environmental and social barriers for wind repowering. Our analysis is supported by a panel of experts with different roles in the wind energy industry. We have scored existing barriers according to their potential impact on the repowering decision. iWe propose a feasible framework of general measures to overcome the identified barriers and promote wind repowering. We conclude that it must be developed a stable regulatory framework for repowering with a focus on the energy efficiency.